![\vec f(x,y,z)=(2yze^{2xyz}+4z^2\cos(xz^2))\,\vec\imath+2xze^{2xyz}\,\vec\jmath+(2xye^{2xyz}+8xz\cos(xz^2))\,\vec k](https://tex.z-dn.net/?f=%5Cvec%20f%28x%2Cy%2Cz%29%3D%282yze%5E%7B2xyz%7D%2B4z%5E2%5Ccos%28xz%5E2%29%29%5C%2C%5Cvec%5Cimath%2B2xze%5E%7B2xyz%7D%5C%2C%5Cvec%5Cjmath%2B%282xye%5E%7B2xyz%7D%2B8xz%5Ccos%28xz%5E2%29%29%5C%2C%5Cvec%20k)
Let
![\vec f=f_1\,\vec\imath+f_2\,\vec\jmath+f_3\,\vec k](https://tex.z-dn.net/?f=%5Cvec%20f%3Df_1%5C%2C%5Cvec%5Cimath%2Bf_2%5C%2C%5Cvec%5Cjmath%2Bf_3%5C%2C%5Cvec%20k)
The curl is
![\nabla\cdot\vec f=(\partial_x\,\vec\imath+\partial_y\,\vec\jmath+\partial_z\,\vec k)\times(f_1\,\vec\imath+f_2\,\vec\jmath+f_3\,\vec k)](https://tex.z-dn.net/?f=%5Cnabla%5Ccdot%5Cvec%20f%3D%28%5Cpartial_x%5C%2C%5Cvec%5Cimath%2B%5Cpartial_y%5C%2C%5Cvec%5Cjmath%2B%5Cpartial_z%5C%2C%5Cvec%20k%29%5Ctimes%28f_1%5C%2C%5Cvec%5Cimath%2Bf_2%5C%2C%5Cvec%5Cjmath%2Bf_3%5C%2C%5Cvec%20k%29)
where
denotes the partial derivative operator with respect to
. Recall that
![\vec\imath\times\vec\jmath=\vec k](https://tex.z-dn.net/?f=%5Cvec%5Cimath%5Ctimes%5Cvec%5Cjmath%3D%5Cvec%20k)
![\vec\jmath\times\vec k=\vec i](https://tex.z-dn.net/?f=%5Cvec%5Cjmath%5Ctimes%5Cvec%20k%3D%5Cvec%20i)
![\vec k\times\vec\imath=\vec\jmath](https://tex.z-dn.net/?f=%5Cvec%20k%5Ctimes%5Cvec%5Cimath%3D%5Cvec%5Cjmath)
and that for any two vectors
and
,
, and
.
The cross product reduces to
![\nabla\times\vec f=(\partial_yf_3-\partial_zf_2)\,\vec\imath+(\partial_xf_3-\partial_zf_1)\,\vec\jmath+(\partial_xf_2-\partial_yf_1)\,\vec k](https://tex.z-dn.net/?f=%5Cnabla%5Ctimes%5Cvec%20f%3D%28%5Cpartial_yf_3-%5Cpartial_zf_2%29%5C%2C%5Cvec%5Cimath%2B%28%5Cpartial_xf_3-%5Cpartial_zf_1%29%5C%2C%5Cvec%5Cjmath%2B%28%5Cpartial_xf_2-%5Cpartial_yf_1%29%5C%2C%5Cvec%20k)
When you compute the partial derivatives, you'll find that all the components reduce to 0 and
![\nabla\times\vec f=\vec0](https://tex.z-dn.net/?f=%5Cnabla%5Ctimes%5Cvec%20f%3D%5Cvec0)
which means
is indeed conservative and we can find
.
Integrate both sides of
![\dfrac{\partial f}{\partial y}=2xze^{2xyz}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20y%7D%3D2xze%5E%7B2xyz%7D)
with respect to
and
![\implies f(x,y,z)=e^{2xyz}+g(x,z)](https://tex.z-dn.net/?f=%5Cimplies%20f%28x%2Cy%2Cz%29%3De%5E%7B2xyz%7D%2Bg%28x%2Cz%29)
Differentiate both sides with respect to
and
![\dfrac{\partial f}{\partial x}=\dfrac{\partial(e^{2xyz})}{\partial x}+\dfrac{\partial g}{\partial x}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20x%7D%3D%5Cdfrac%7B%5Cpartial%28e%5E%7B2xyz%7D%29%7D%7B%5Cpartial%20x%7D%2B%5Cdfrac%7B%5Cpartial%20g%7D%7B%5Cpartial%20x%7D)
![2yze^{2xyz}+4z^2\cos(xz^2)=2yze^{2xyz}+\dfrac{\partial g}{\partial x}](https://tex.z-dn.net/?f=2yze%5E%7B2xyz%7D%2B4z%5E2%5Ccos%28xz%5E2%29%3D2yze%5E%7B2xyz%7D%2B%5Cdfrac%7B%5Cpartial%20g%7D%7B%5Cpartial%20x%7D)
![4z^2\cos(xz^2)=\dfrac{\partial g}{\partial x}](https://tex.z-dn.net/?f=4z%5E2%5Ccos%28xz%5E2%29%3D%5Cdfrac%7B%5Cpartial%20g%7D%7B%5Cpartial%20x%7D)
![\implies g(x,z)=4\sin(xz^2)+h(z)](https://tex.z-dn.net/?f=%5Cimplies%20g%28x%2Cz%29%3D4%5Csin%28xz%5E2%29%2Bh%28z%29)
Now
![f(x,y,z)=e^{2xyz}+4\sin(xz^2)+h(z)](https://tex.z-dn.net/?f=f%28x%2Cy%2Cz%29%3De%5E%7B2xyz%7D%2B4%5Csin%28xz%5E2%29%2Bh%28z%29)
and differentiating with respect to
gives
![\dfrac{\partial f}{\partial z}=\dfrac{\partial(e^{2xyz}+4\sin(xz^2))}{\partial z}+\dfrac{\mathrm dh}{\mathrm dz}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cpartial%20f%7D%7B%5Cpartial%20z%7D%3D%5Cdfrac%7B%5Cpartial%28e%5E%7B2xyz%7D%2B4%5Csin%28xz%5E2%29%29%7D%7B%5Cpartial%20z%7D%2B%5Cdfrac%7B%5Cmathrm%20dh%7D%7B%5Cmathrm%20dz%7D)
![2xye^{2xyz}+8xz\cos(xz^2)=2xye^{2xyz}+8xz\cos(xz^2)+\dfrac{\mathrm dh}{\mathrm dz}](https://tex.z-dn.net/?f=2xye%5E%7B2xyz%7D%2B8xz%5Ccos%28xz%5E2%29%3D2xye%5E%7B2xyz%7D%2B8xz%5Ccos%28xz%5E2%29%2B%5Cdfrac%7B%5Cmathrm%20dh%7D%7B%5Cmathrm%20dz%7D)
![\dfrac{\mathrm dh}{\mathrm dz}=0](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20dh%7D%7B%5Cmathrm%20dz%7D%3D0)
![\implies h(z)=C](https://tex.z-dn.net/?f=%5Cimplies%20h%28z%29%3DC)
for some constant
. So
![f(x,y,z)=e^{2xyz}+4\sin(xz^2)+C](https://tex.z-dn.net/?f=f%28x%2Cy%2Cz%29%3De%5E%7B2xyz%7D%2B4%5Csin%28xz%5E2%29%2BC)